METHOD AND MEDIA USED IN TEACHING VOCABULARY AT TAMAN INDRIA IBU PAWIYATAN ACADEMIC YEAR 2012-2013 YOGYAKARTA - Tuti Tuti (STKIP Persada Khatulistiwa Sintang, 2019)
Vocabulary is one of the essential elements in learning language. Survey data shows that students in kindergarten not easy to memorize new vocabulary. Therefore, researcher tries to analyze the method and media used by the teacher in teaching vocabulary. The objectives of the study are 1) to find out the methods and media that are used by the teacher in teaching vocabulary at Taman Indria Kindergarten. 2) to know the underlying reason of the teacher using those methods and media in teaching vocabulary.The research approach is qualitative, with the research method used is descriptive. The study population was students of Taman Indria children age 3-5 years old the class consist of 20 students. The data were collected through observation, checklist, field note, video transcription and interview. The data were analyzed based on the characteristics of the methods which teacher applied in every activity. The results of the research showed that the teacher in Taman Indria mostly used Direct method and Total physical respond meanwhile, media that she used is whiteboard and picture.Keywords: teacher; young learner; vocabulary; method; media